2022
DOI: 10.1002/ejoc.202200454
|View full text |Cite
|
Sign up to set email alerts
|

Iron–Copper Dual Catalysis Enabling C−C and C−X (X=N, B, P, S, Sn) Bond Formation

Abstract: Dedicated to Professor Zhen Yang on the occasion of his 63rd birthdayThe dual-catalysis tactics where two types of catalysts are connected in one single reaction operation are highly prized in the novel bond constructions that are difficult or unattainable to be achieved with current mono-catalysis. In recent years, increased emphasis on sustainable catalytic methods on more economic and eco-friendly processes has shifted the focus to catalysis with earth-abundant transition metals, such as iron, copper, and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 116 publications
1
5
0
Order By: Relevance
“…During individual fish development, changes occur in its food intake and digestive organs (Wootton, 1998). Many studies have shown that as fish grow and develop, their feeding habits are generally transformed (Graeb et al, 2005;Yan et al, 2011;Huo et al, 2014;Su et al, 2015;Sarker et al, 2023). Different sizes of fish have different food preferences (different prey types and sizes), which are related to the strategy of predation (Graeb et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During individual fish development, changes occur in its food intake and digestive organs (Wootton, 1998). Many studies have shown that as fish grow and develop, their feeding habits are generally transformed (Graeb et al, 2005;Yan et al, 2011;Huo et al, 2014;Su et al, 2015;Sarker et al, 2023). Different sizes of fish have different food preferences (different prey types and sizes), which are related to the strategy of predation (Graeb et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The stomach content analysis is a traditional method for studying fish feeding, and it is also the most direct and effective. It can accurately determine specific types of diet and is widely used in studies of fish feeding ecology (Yan et al, 2011;Huo et al, 2014;Ma et al, 2014;Sui et al, 2021;Sarker et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Although most bimetallic catalysts reported until date are based on heterogeneous catalysis, 22−24 reports of their discrete molecular species being involved and detected in homogeneous catalysis, especially in C−H activation processes. 25,26 A study of the literature with respect to directing group assistance leads to the conclusion that when there is scope for two different sites for functionalization, the observed selectivity is dependent on several factors, such as the nature of the directing group and the catalyst employed. The directing groups at C3 reported to date are linked to the indole via C−C bonds and involve indolyl imines, aldehydes, ketones, carboxylic acids, or their esters.…”
Section: ■ Introductionmentioning
confidence: 99%
“…A bimetallic catalyst involves two metals acting synergistically to provide a better yield and selectivity of the product compared to those of any one of them. Although most bimetallic catalysts reported until date are based on heterogeneous catalysis, there are some reports of their discrete molecular species being involved and detected in homogeneous catalysis, especially in C–H activation processes. , …”
Section: Introductionmentioning
confidence: 99%
“…[3] Among them, dual-catalysis wherein two catalysts cooperatively activate reacting partners in the discrete catalytic cycles appears to be very promising strategy. [4] Such cooperative dual catalysis has shown unprecedented reactivity for the functionalization of CÀ H bonds in various synthetically challenging conversions. [5] Recently, cooperative bimetallic mechanism involving two distinct palladium centers has also been explored.…”
Section: Introductionmentioning
confidence: 99%